Thiamine supplement therapy improves ejection fraction value in stage ii heart failure patients - Jikrona, Rafi; Suharjono, Suharjono; Ahmad, Abraham (Folia Medica Indonesiana, 2017)
Thiamine, also called vitamin B1, is a water soluble vitamin that is involved in the formation of ATP in cells. The active metabolite of thiamine is a co-enzyme thiamine pyrophosphate (TPP) that plays an active role in carbohydrate metabolism and the formation of amino acid binding conjugates. Directly, thiamine may increase energy production in heart muscle cells through such mechanism, whereas in conditions of heart failure, a decrease in the contractility of heart muscle may be found. Therefore, thiamine supplementation is needed in stage II heart failure patients due to long-term use of furosemide that triggers the thiamine deficiency condition. Thiamine supplementation here is enabled to increase heart cells contractility which may ultimately increase the ejection fraction value of the heart muscle as a parameter of heart work efficiency measurement. The objective of this study was to evaluate the effect of thiamine administration as a therapeutic supplement in stage II of heart failure patients on the ejection fraction rate changes in pre and post thiamine supplement therapy for 28 days. The study was conducted using Cross Sectional Prospective Observational Analysis method between April and August 2016 in male patients with NYHA II heart failure who received furosemide therapy meeting the inclusion criteria at Heart Clinic Jemursari Islamic Hospital, Surabaya. Patients who fulfilled the inclusion and exclusion criteria in this study were 32 patients, 16 control patients and 16 treatment group patients between the ages of 35-75 years. During this study, after supplementation of thiamine 300 mg/day, 16 patients in the treatment group experienced an increase in ejection fraction rate (13.5%). The result of paired t test p=0.000 (p<α; α=0,05) showed significant difference between ejection fraction rate of pre and post thiamin supplementation. This study concluded that thiamine supplement therapy of 300 mg/day could increase the ejection fraction rate in patients of stage II heart failure.